Exosomes as the promising biomarker for Epstein-Barr Virus (EBV)-associated cancers - Teow, Sin Yeang *; Peh, Suat Cheng * (InTech Open Publisher, 2017)
Exosomes are microvesicles with sizes ranging from 50 to 150 nm. These small vesicles are known to morphologically and functionally resemble virus particles from human immunodeficiency virus type I (HIV-I) and human T-lymphotropic virus type I (HTLV-I). The function of exosomes is to mainly mediate cell-to-cell communication by exchanging various macromolecules including proteins, lipids and nucleic acids in diverse cellular processes. Due to its size and structural simplicity, the transfer of pathogenic or virulent cellular factors across the cells mediated by exosomes is more efficient, hence facilitating the dissemination of viral infections and cancer diseases. The pathogenic role of exosomes in various cancers such as lung and breast, and their potentials as biomarkers have been previously studied, yet limited information is known for Epstein-Barr virus (EBV)-associated cancers. In this chapter, we discuss current evidences that support the pathogenic roles of exosomes in EBV-related cancers and their potentials as biomarkers in cancer diagnostics and therapy response. Here, we also highlight the potential challenges in the development of exosome-based biomarkers for clinical application.